La première maison d’Amazonie. Le Formatif dans la province de Pastaza, Équateur - Stéphen Rostain; Geoffroy de Saulieu (Journal de la Société des Américanistes)
The interdisciplinary project entitled « Zulay, the pre-Columbian portal to the Amazon », in the upper valley of the Pastaza (Ecuadorian Amazon), has led to the discovery and extensive excavation of the remains of a late Formative house, dated cal. 1496-1302 BC. The study of the distribution of postholes, pits, and stone-made hearth has enabled archaeologists to reconstruct a dwelling pattern similar to that of present indigenous houses in the area. In addition, one end of a perfectly preserved wooden post has been found at an undisturbed cross section at groundwater level. It consists of a trimmed tree trunk, which was placed upside down in the ground, the crown towards the earth. Due to the scarcity of pre-Columbian domestic structures that have been studied in the region, the discovery of one of the most ancient Amazonian houses constitutes a remarkable finding.